LATAR BELAKANG KECEMASAN ANAK PRA SEKOLAH KASUS A (IM) SISWA TAMAN KANAK-KANAK AR-RAHMAH PALEMBANG - Aslam Tamisa (Psikis : Jurnal Psikologi Islami, 2016)
he  reseach  aims  to  find  out  the  background  of  pre-school  children's  anxiety  cases  A kindergarten student Ar-Rahmah Palembang. The problem of being discussed is how background anxiety pre-school children. This reseach was a qualitative case study. Data collection techniques using  observation,  interviews,  documentation,  and  analysis  using  the  concept  of  "fish  bone"  is looking for the cause of anxiety. Comparing data observations with interviews, compares the results interview delivered in public with what is said in private, and comparing sources perspective with expert opinions psychology. Results of research conducted on a pre-school children Kindergarten students  obtained  the  information  came  from  families  where  both  parents  work  in  a  private company  from  morning  until  afternoon,  had  an  attitude  and  behavior  that  makes  the  subject  is always full of excessive fear. Subjects behave like screaming, aloof, evasive and not able to be with his friends, cold hands or palms are always wet, often to the bathroom with no apparent reason. His parents, especially the father always angry rebuke and erratically toward the subject so that the subject  is  always  crying  for  attention  excess  of  teachers  in  schools.  Conclusion  experienced subjects is excessive anxiety, need attention and affection from their parents, as  well as applying parenting attached to embed principles such as compassion positive touch, sensitivity to the needs of children, and to have time with the child.